2000
DOI: 10.1038/35011002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for genetic mixing of Arctic and Antarctic subpolar populations of planktonic foraminifers

Abstract: Bipolarity, the presence of a species in the high latitudes separated by a gap in distribution across the tropics, is a well-known pattern of global species distribution. But the question of whether bipolar species have evolved independently at the poles since the establishment of the cold-water provinces 16-8 million years ago, or if genes have been transferred across the tropics since that time, has not been addressed. Here we examine genetic variation in the small subunit ribosomal RNA gene of three bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
252
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(277 citation statements)
references
References 27 publications
12
252
1
5
Order By: Relevance
“…More recent glacial events may have also favored genetic exchange between the Polar Regions, as suggested for cold-water foraminifers (Darling et al, 2000), although such cooling could also lead to isolation and divergence of some populations (Darling et al, 2004), and dinoflagellates (Montresor et al, 2003).…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 99%
“…More recent glacial events may have also favored genetic exchange between the Polar Regions, as suggested for cold-water foraminifers (Darling et al, 2000), although such cooling could also lead to isolation and divergence of some populations (Darling et al, 2004), and dinoflagellates (Montresor et al, 2003).…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 99%
“…Thus, molecular analyses of marine foraminifera evince not only regional affinities consistent with physical or ecological limits to gene flow (Darling et al 2007) but also long-distance dispersal (e.g. Darling et al 2000;Esteban et al 2007; see also Brown & Hovmøller 2002). Most studies to date suggest that neither marine nor soil bacteria show the latitudinal diversity gradient (Baldwin et al 2005;Fierer & Jackson 2006), but there are recent exceptions (Pommier et al 2007) which may be common among larger microbes (e.g.…”
Section: Comparing Marine and Terrestrial Organisms In Physically Simmentioning
confidence: 99%
“…Ely et al 2005;Goetze 2005 and 15 references therein) and this aspect of ocean evolution thus represents a 'serious challenge' to the idea of allopatric speciation (Palumbi 1994;see also Goetze 2005), which is often considered the predominant mode of speciation in terrestrial organisms (Mayr 1954(Mayr , 1963Winston 1999, p. 48;see Schilthuizen 2001, p. 186). However, advances in our understanding of oceanography and marine molecular ecology are increasingly revealing that the ocean is more physically heterogeneous than we thought, with shorter dispersal, smaller geographical ranges, smaller population sizes and lower gene flow (Rosenblatt 1963;Field et al 1997;Longhurst 1998;Jones et al 1999;Darling et al 2000;Carr et al 2003;Selje et al 2004;Goetze 2005). It is now clear that geographical speciation-including allopatric, parapatric and/or peripatric speciation-is common also in marine taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Galand et al (2010) reported of a strong association between the large-scale distribution of microbial communities from the deep Arctic and the hydrogeography of the arctic water masses. Differences in community structure would thus reflect the differences in environmental parameters among water masses, as also suggested by studies of marine foraminiferans (De Vargas et al, 1999;Darling et al, 2000). Schauer et al (2009), who studied the same sampling regions of the South-East Atlantic, attributed the differences reported, at least partially, to environmental differences of the different water masses.…”
Section: Discussionmentioning
confidence: 90%